2019
DOI: 10.1007/s40496-019-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-Malignant Blood Disorders and Their Impact on Oral Health: an Overview

Abstract: Purpose of Review This review aims to summarize the literature on inherited hemoglobin and coagulation disorders, focusing on sickle cell disease (SCD), thalassemia, hemophilia, and von Willebrand disease (vWD), and their impact on oral health. Clinical dental management of patients with these conditions is also reviewed. Recent Findings There is no evident association between caries and SCD. Despite limited available studies, there may be a possible association between caries and thalassemia, which could rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Hematological conditions comprise a wide range of disorders that can be classified as nonmalignant (anemia, hemorrhagic, or thrombotic disorders and conditions affecting blood-forming organs) and malignant (hematological cancers, such as Hodgkin and non-Hodgkin lymphoma, leukemia, or multiple myeloma, among others) [14]. These diseases meet all criteria for qualifying as a very important public health problem, with serious morbidities affecting patients worldwide [14][15][16]. Many of these conditions, such as hemophilia or anemia, are highly prevalent and become chronic.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological conditions comprise a wide range of disorders that can be classified as nonmalignant (anemia, hemorrhagic, or thrombotic disorders and conditions affecting blood-forming organs) and malignant (hematological cancers, such as Hodgkin and non-Hodgkin lymphoma, leukemia, or multiple myeloma, among others) [14]. These diseases meet all criteria for qualifying as a very important public health problem, with serious morbidities affecting patients worldwide [14][15][16]. Many of these conditions, such as hemophilia or anemia, are highly prevalent and become chronic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that thalassemic patients are susceptible to dental caries because their caries index is high and they have significantly low salivary phosphorous and IgA concentration [4,28]. This occurs because patients are hesitant to visit a dentist for fear of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Nutritional anemia is mainly associated with the deficiency of iron, vitamin B 12 , folic acid, hormones, other vitamins, and minerals, whereas hemolytic anemia occurs due to premature RBCdestruction and aplastic anemia is due to bone marrow failure. 20 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…3,19 Non-malignant hematological disorders are agroup of diverse conditions ranging from inherited conditions like hemophilia and sickle cell disease to common non-hereditary conditions such as venous thromboembolism and different types of anemia. 20 Anemia is the condition associated with reduced numbers of red blood cells (RBC) or decreased hemoglobin level (Hgb) and it can be grouped into different categories based on the cause such as nutritional, hemolytic, and aplastic anemia. 21,22 Nutritional anemia is mainly associated with the deficiency of iron, vitamin B 12 , folic acid, hormones, other vitamins, and minerals, whereas hemolytic anemia occurs due to premature RBCdestruction and aplastic anemia is due to bone marrow failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation